2021
DOI: 10.1002/micr.30713
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of functional outcomes in rat sciatic nerve injury models

Abstract: Introduction Rat sciatic nerve injury (PNR) is the most utilized model in studies on peripheral nerve regeneration. However, large animal models are increasingly favored based on the assumption that nerve regeneration in rodents achieves more favorable outcomes than in humans. The purpose of this meta‐analysis was to investigate which rat PNR models are more stringent and should be used before utilizing large animal experimentation. Methods A PRISMA‐guided meta‐analysis of the English literature regarding func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“… Brenner et al (2008) demonstrated that while the nerve regenerative effect of tacrolimus is significant at 40 days, it is undetectable at 70 days. Similar results are found in a metanalysis by DeLeonibus et al, 2021 .…”
Section: Challenges For Translating New Ngc Designs Beyond Preclinica...supporting
confidence: 90%
“… Brenner et al (2008) demonstrated that while the nerve regenerative effect of tacrolimus is significant at 40 days, it is undetectable at 70 days. Similar results are found in a metanalysis by DeLeonibus et al, 2021 .…”
Section: Challenges For Translating New Ngc Designs Beyond Preclinica...supporting
confidence: 90%
“…Best functional outcomes were observable following direct nerve coaptation in end-to-end technique, mirroring results of primary repair of the median nerve in humans [ 40 ]. Like sciatic nerve models, second best outcomes were obtained following autograft repair of segmental nerve injuries [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of peripheral nerve injury are essential to expand our understanding of neural regeneration following therapeutic interventions, which we continuously strive to improve, given the dramatic impact of peripheral nerve injuries on the affected patients’ quality of life [ 1 , 2 , 3 ]. The most frequently used rodent model to study peripheral nerve injury and regeneration is the sciatic nerve of the rat [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of increase in the deformities in the rats' hind limbs was faster than the restimulation of the muscles by the repaired sciatic nerve. Rat sciatic nerve models are known to be adequate to provide translatable information; however, SFI remains incapable of objectively evaluating functional recovery (DeLeonibus et al, 2021). Navarro reported that the possibilities of evaluating the functional recovery of motor skills after sciatic nerve injury in the awakened animal are rather limited or need considerable efforts to be realized (Navarro, 2016).…”
Section: Discussionmentioning
confidence: 99%